Higher Hydrocarbon Production through Oxidative Coupling of Methane Combined with Hydrogenation of Carbon Oxides. Issue 11 (1st September 2014) - Albrecht, Matthias; Rodemerck, Uwe; Kondratenko, Evgenii V.
Abstract In the production of higher hydrocarbons, combining oxidative coupling of methane (OCM) with hydrogenation of the formed carbon oxides in a separate reactor provides an alternative to the currently applied methane conversion to syngas followed by Fischer‐Tropsch synthesis. The effects of CH4:O2 feed ratio in the OCM reactor and partial pressures of H2 or/and H2O in the hydrogenation reactor were analyzed to maximize production of C2+ hydrocarbons and reduce COx formation. The highest C2+ yield was achieved with low CH4:O2 feed ratio for OCM and removal of the formed water before entering the hydrogenation reactor.